Cifrovìzacìâ mìscevogo samovrâduvannâ v Ukraïnì: potencìal ì vikliki v umovah vìjni - Koroliuk, Tetiana; Kovpak, Andrii (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In this article the authors analyze the processes of digital transformation of local government in Ukraine, identify the problems that lead to the formation of digital barriers, and outline the directions for further digital development in communities. Particular attention is paid to ad-dressing the need to introduce digital tools into the practice of interaction between authorities and communications with community residents in the context of the information revolution, the rapid development of information and communication technologies, and the growth of global inequality in the context of deepening global digital divides. It was noted that the primary steps on the way to the digital development of the community should be assessing the community’s readiness to implement digital changes and developing a digital transformation strategy together with a development strategy for digital education.
Keywords: local government; digital transformation; e-government; digital tools; digital education; mìsceve samovrâduvannâ; cifrova transformacìâ; elektronne vrâduvannâ; cifrovì ìnstrumenti; cifrova osvìta